Training wildlife biologists for work on private lands - Brown, Mary Bomberger, speaker; Smith, Jennifer A., speaker; Powell, Larkin A., speaker; Calderazzo, John, moderator; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
Conservation and management of wildlife on private lands in the United States is a critical component of the wildlife profession, although university curricula focus on public lands management. Wildlife biologists working on private lands are faced with a mutable landscape and pressures of alternative land uses that shift with changes in economics, regulatory regimes, and societal or cultural values. Loss of biodiversity can be lessened if wildlife biologists are better prepared to work in this challenging landscape. Colleges and universities are faced with training wildlife biologists to work on both public and private lands. Unfortunately, however, wildlife training programs often fail to integrate the management techniques, policy, economics, human dimensions, problem solving, and communication skills required by private lands professionals. Of 14 leading undergraduate wildlife programs that we identified, 36% required a policy class, 36% required a human dimensions class and 7% required an economics class; although most universities did offer interdisciplinary courses, participation was seldom mandatory. We suggest that students and current professionals need to be trained in the skills necessary to protect wildlife when working on privately owned lands. We highlight tools needed for effective private lands conservation such as economic incentives, education, and outreach, and we suggest ways in which they can be taught through modifications to current curriculum, short-courses, continuing education credits, certificate programs, internships, externships, and involvement of agency personnel in the classroom.
Moderator: John Calderazzo.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
Video presenter: Jennifer Smith.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses